Chapter Funduq, Fondaco, Feitoria. The Portuguese Contribution to the Globalisation of an Institution of Overseas Trade - Sicking, Louis (Atti delle «Settimane di Studi» e altri Convegni, 2019)
A particular kind of institutions contributed importantly to the organisation of overseas trade: funduqs and fondacos which originated around the medieval Mediterranean. This article aims to contribute to the debate on these institutions. This will be done by looking at the Portuguese feitoria, which may be considered as the missing link between the medieval Mediterranean institutions known as funduqs and fondacos and the early modern factories overseas. This allows to shed new light on relations and entanglements between different seascapes and thus to contribute to the fields of new institutional economics and global history.